A New N-Substituted 1H-Isoindole-1,3(2H)-Dione Derivative—Synthesis, Structure and Affinity for Cyclooxygenase Based on In Vitro Studies and Molecular Docking - Szkatuła, Dominika (Int J Mol Sci, 2021)
Isoindoline-1,3-dione derivatives constitute an important group of medicinal substances. In this study, nine new 1H-isoindole-1,3(2H)-dione derivatives and five potential pharmacophores were obtained in good yield (47.24–92.91%). The structure of the new imides was confirmed by the methods of elemental and spectral analysis: FT–IR, H NMR, and MS. Based on the obtained results of ESI–MS the probable path of the molecules decay and the hypothetical structure of the resulting pseudo-molecular ions have been proposed. The physicochemical properties of the new phthalimides were determined on the basis of Lipiński’s rule. The biological properties were determined in terms of their cyclooxygenase (COX) inhibitory activity. Three compounds showed greater inhibition of COX-2, three compounds inhibited COX-1 more strongly than the reference compound meloxicam. From the obtained results, the affinity ratio COX-2/COX-1 was calculated. Two compounds had a value greater than that of meloxicam. All tested compounds showed oxidative or nitrosan stress (ROS and RNS) scavenging activity. The degree of chromatin relaxation outside the cell nucleus was lower than the control after incubation with all test compounds. The newly synthesized phthalimide derivatives showed no cytotoxic activity in the concentration range studied (10–90 µM). A molecular docking study was used to determined interactions inside the active site of cyclooxygenases.